2009
DOI: 10.1007/s10856-009-3804-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ca/P ratio and milling material on the mechanochemical preparation of hydroxyapaptite

Abstract: The mechanochemical transformation of Ca(OH)(2)-(NH(4))(2)HPO(4) with different Ca/P ratios 1; 1.5; 1.67 and 1.75 was carried out for different periods of time from 10 min to 24 h in a horizontal vibration mill using steel and agate vials and balls. The phase transformations obtained at each milling stage were characterized by X-ray diffraction, infrared spectroscopy and transmission electron microscopy. Complete transformation to hydroxyapatite took place during the first 5 h of milling, for Ca/P ratios 1.5 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…1020 and 560 /cm regions (see Figure 4). The N-H does not appear significantly in either the range of 3300-2800 /cm or 1456-1400 /cm as Salas et al found [10], it may be the condition there and here are different like that people found carbonate systems in different regions between dry and wet processes.…”
Section: Discussionmentioning
confidence: 48%
“…1020 and 560 /cm regions (see Figure 4). The N-H does not appear significantly in either the range of 3300-2800 /cm or 1456-1400 /cm as Salas et al found [10], it may be the condition there and here are different like that people found carbonate systems in different regions between dry and wet processes.…”
Section: Discussionmentioning
confidence: 48%
“…The results of the investigation using EDS, after each treatment stage (at three points on the sample surface), are presented in Figure 2 and Table 1. The Ca/P ratio on the surface was 1.7, in which the mean ratios Ca/P = 1.67 [14,15] were indicated. The study of the processes involved in the formation of hydroxyapatite crystals on the titanium surface provides evidence that their inception depends on the number of surface hydroxyl groups present [4].…”
Section: Resultsmentioning
confidence: 94%
“…There were several synthesis techniques that have been reported in synthesis Mg-doped HA such as precipitation [4], and sol-gel [7]. Mechanochemical method is a simple method in powder synthesis especially in a dry condition [8,91. This study reports the HA and Mg doped HA powders synthesized through dry mechanochemical method and the effect of M~~~ to the synthesized powder properties of HA.…”
Section: Magnesium Ion ( M~~+ )mentioning
confidence: 99%